A novel network selection mechanism for vehicle-to-infrastructure communication - Ndashimye, E; Sarkar, NI; Ray, SK (IEEE, 2016)
The commercial deployment of 5G networks require heterogeneous multi-tier, multiple radio access technologies (RATs) to support vehicle-to-infrastructure (V2I) communication with diversified services. Vehicles may need to cross a number of heterogeneous networks of various sizes before reaching the destination. Due to high-speed travel, vehicles may quickly move in and out of the network coverage areas while performing handover. Fast and efficient selection of an appropriate underlying network is critical for seamless handover performance. In this paper we propose a novel network selection mechanism for improved handover performance in V2I communication over heterogeneous wireless network. The idea is for vehicles to self-evaluate a candidate list of access points (AP) that are located in the vehicle movement direction and select the best underlying candidate network based on key criteria, like, the distance between target candidate and the trajectory of the vehicle movement as well as the vehicle mobility information. Fuzzy logic inference system is used to decide whether a target candidate is suitable for handover. Experimental results show that for a vehicle moving at 30km=h, an AP of 100m radius should be located at less than 30m from the road, while this distance is limited to 15m when the vehicle speed is 60km/h.
Keywords: V2I; Multi-tier network; Heterogeneous RATs Macro-cell; Small cells; Handover; Fuzzy logic